AKAR-AKAR TRADISI POLITIK SUNNI DI INDONESIA - Muhammad Iqbal (Al Qalam, 2009)
The Sunni doctrine plays an important role in the government. Its accommodative characteristic is something important that makes Sunni doctrine to be a device of the legitimation of the authority. The Muslim thinkers of classical Sunni such as al-Mawardi (975-1058 M), al-Ghazali (1058-1111 M) and lbn Taimiyah(1263-1329 M) have a great role in formulating the political doctrine of Sunni. In spite of the different nuance, all of these three classical Sunni thinkers develop the moderate political doctrine of Sunni. On the one hand, it is, of course, significant in situating the harmonious relation between the ruler and community. Therefore, the social and political stabilities will be well-maintained On the other hand, such a thought for a certain extent evokes stagnancy. Because there is no radical thought which is critical and opposite against the authority, the Sunni idea is frequently made use for the instantaneous interests of power. On evenlttally, the mutual interrelationship between the Sunni ulama and the ruler often happens. While ulama feel obtaining the patronage from the authority, the ruler gains religious justification from ulama. In this context, Indonesia as the country with the majority of Sunni Muslims, as a matter of fact, applies the political doctrine of Sunni. It is because Sunni has had a long and establishei root since. the period of Islamic kingdoms in the archipelago, before Dutch-Colonial period. The archipelago ulama also formulated the harmonious relation between Islam and authority as formulated by the ulama of classical Sunni. The polotical tradition of Sunni was becoming stronger in line with the great influence of ulama in the archipelago kingdoms. This article tries to elaborate the relation between the Sunni ulama with the power of the kings in the archipelago and the patronage of the archipelago rulers toward them.